The Relationship between Iron Deficiency and Nutritional Status of Elementary School Children in the Tuah Negeri District - Riska Umami; Rostika Flora; Rico Januar Sitorus; Mohammad Zulkarnain (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
During a child's growth period, iron is very necessary. High iron requirements during growth must be supplemented by adequate iron intake. Stunting in children is related to the lack of iron in their food. The objective of this study is to examine the relationship between iron deficiency and nutritional status among elementary school students in the Tuah Negeri District. This study was an analytic observational study with a cross-sectional design. A sample of 79 people was taken randomly from elementary school students in Tuah Negeri District. The determination of iron deficiency in children is done by examination of serum iron using the ELISA method while the nutritional status was determined based on high-for-age measurement. SPSS version 16 was used to analyze the data, which included Univariate, Bivariate, and Multivariate analysis. The results of the measurement of serum iron levels showed that 65.6% of children with iron deficiency were stunted, while in children who were not iron deficient, only 29.8% were stunted. There was a significant relationship between iron deficiency and nutritional status in children (p=0.004; OR=4,500). Multivariate test results showed that iron deficiency was the most dominant factor associated with nutritional status in children. There was a relationship between iron deficiency and the nutritional status of elementary school children in Tuah Negeri District., and recommended to increase health promotion efforts related to the importance of iron intake for the growth of children.